Microsoft PowerPoint Media Use and Student Learning Motivation in Islamic Religious Education - Asep Sulaeman (STAI Hubbulwathan Duri, 2021)
This study aimed to analyze using Microsoft Powerpoint computer media on students' learning motivation in Islamic Religious Education subjects. The approach used in this study is quantitative. The data used in this study, namely the use of Microsoft Powerpoint media and students' learning motivation in religious education at a private Junior High School in Garut Regency, was analyzed in the form of statistical data. The method used in this research is the descriptive method. Based on the data analysis, it can be concluded as follows: 1) The use of Microsoft PowerPoint media is well proven and reduce verbalism, teaching materials are more transparent in meaning; 2) The more explicit motivation of students is in the excellent, as evidence by excellent results of research on the indicators of being diligent, tenacious, happy to work independently, confident and happy to find and solve problems showing a number 4.09. This figure is in the interval 3.5 – 4.5, including good category; and, 3) The use of Microsoft PowerPoint media on students' motivation to learn is good. It is proven that the study results show that 57% is in a suitable category. As for 43%, it is influenced by other factors.